Embedment strength of smooth nails in timber construction – Characteristic and mean values. (23rd May 2022) - Iwuoha, Stanley Emeka; Seim, Werner
Highlights: Going from the mean to the characteristic embedment strength values by replacing the mean density value with the characteristic density value is an incorrect procedure. The existing equations for determining the characteristic embedment strength of timber yields results which are 14.3% and 19% higher than the actual characteristic embedment strength values for the non-predrilled and predrilled cases respectively. Equations which define the actual characteristic embedment strength of timber have been determined, discussed, and validated using two independent scientific methods. Abstract: Studies have been conducted on the embedment strength of timber. However, those dealing with small diameter dowel type fasteners, particularly the transition from mean to characteristic values are lacking. This study is an investigation into the embedment strength of small diameter dowel type fasteners; with a focus on discussing the procedure of going from mean to characteristic values. Questions about the derivation of the existing embedment strength equations were discussed and some dark areas were clarified. Using two independent statistical methods and 14 test series, the inter-connection between the mean and characteristic embedment strength values was investigated. The investigations showed that the characteristic embedment strength values obtained by replacing the mean density with the characteristic density values in established equations, yield values which are higher than the actual characteristic values by an average of 14% and 19% for the non-predrilled and predrilled cases respectively. Detailed explanations to these findings were given and proposals with reference to the existing equations were presented and discussed.